Evolution of macular microvasculature and retinal layers alterations in patients with macula off retinal detachment after vitrectomy. Issue 1 (January 2022) - Chatziralli, Irini; Theodossiadis, George; Chatzirallis, Alexandros; Dimitriou, Eleni; Parikakis, Efstratios; Theodossiadis, Panagiotis
Purpose: To examine the changes in retinal microvasculature in association with retinal layers' condition in patients with rhegmatogenous retinal detachment (RRD) treated with pars plana vitrectomy (PPV). Methods: Participants in this study were 89 patients with macula off RRD, who were successfully treated with PPV and gas tamponade without internal limiting membrane peeling, in two centers. All participants underwent best corrected visual acuity (BCVA) measurement, slit-lamp examination, fundoscopy, spectral domain-optical coherence tomography (SD-OCT) and optical coherence tomography angiography (OCTA) at week 5, month 3 and month 6 postoperatively. The fellow untreated eyes were also examined and served as control data. Results: A statistically significant enlargement in foveal avascular zone (FAZ) in both superficial capillary plexus (SCP) and deep capillary plexus (DCP), accompanied with a statistically significant thinning of inner retinal layers, was noticed 5 weeks postoperatively. These changes, namely FAZ enlargement and thinning of inner retinal layers, in the operated eyes compared to the fellow eyes, remained unchanged till month 6 postoperatively. BCVA improved significantly from week 5 to months 3 and 6 postoperatively. The improvement in BCVA was associated with the gradual ellipsoid zone (EZ) recovery from the first (week 5) till the last examination (month 6). Conclusions: The FAZ enlargement in the operated eyes was accompanied with a statistically significant thinning in the inner retinal layers. Inter-correlation of BCVA and EZ integrity was noticed.